A history of failure and repairs of the reinforced concrete raw coal silo. (October 2019) - Hulimka, Jacek; Kałuża, Marta
Highlights: A case of structural failure of RC silo for raw coal is presented and analyzed. Inspections, test and calculation were performed to assess the condition of the silo. Several reasons explaining the state of the structure have been identified. The failure was caused by negligence in use and maintenance. Possible scenarios of use and successive remedial actions have been discussed.